Critical Pedagogy in Islamic Education: Re-examining the Thought of Paulo Freire and Ibn Khaldun for Liberatory Learning - Dian Nopita Sari; Sefri Kandi Ja’far Yazid; Adelia Syafitri; Atmajaya; Akbar Maulidin; Irma; Muhammad Abid Fathin (Sustainable, 2024)
Contemporary Islamic education frequently struggles with authoritarian, rote-learning practices that fundamentally contradict its emancipatory theological ideals. This study aims to resolve this pedagogical stagnation by synthesizing Paulo Freire’s critical pedagogy with Ibn Khaldun’s humanistic educational philosophy. Employing a qualitative library research method with a comparative-philosophical approach, the study critically analyzes primary texts and recent scholarly literature published between 2019 and 2024. The findings reveal that while Freire offers robust socio-political conscientization, it inherently lacks spiritual depth. Conversely, Ibn Khaldun provides essential psychological safety and gradual learning but requires a critical edge for modern social justice. By integrating both paradigms, this research proposes a novel conceptual framework termed "Prophetic Critical Pedagogy." This integrated model successfully marries structural liberation with spiritual transcendence, transforming the classroom into a dynamic space for dialogic inquiry and moral action. Ultimately, this framework offers Islamic educational institutions a transformative pathway to cultivate critically conscious, morally grounded, and socially responsible learners, effectively bridging the epistemological gap between classical Islamic wisdom and modern critical theory.